MODAL OPERATORS ON BIPOLAR FERMATEAN FUZZY MATRICES - K. Lalitha; S. Sathya; S. Sarguna (Utilitas Mathematica, 2025)
In this section, necessity and possibility operators are formulated for Bipolar Fermatean Fuzzy matrices, and various algebraic operations are discussed. Additionally, the complement of the matrix is studied using modal operator combinations.